Prescreening with FOBT Improves Yield and Is Cost-Effective in Colorectal Screening in the Elderly. (6th April 2014) - Singhal, Shashideep; Changela, Kinesh; Basi, Puneet; Mathur, Siddharth; Reddy, Sridhar; Momeni, Mojdeh; Krishnaiah, Mahesh; Anand, Sury
Abstract : Background . Utilization of colonoscopy for routine colorectal cancer (CRC) screening in the elderly (patients over 75) is controversial. This study was designed to evaluate if using fecal occult blood test (FOBT) to select patients for colonoscopy can improve yield and be a cost- effective approach for the elderly. Methods . Records of 10, 908 subjects who had colonoscopy during the study period were reviewed. 1496 (13.7%) were ≥75 years. In 118 of these subjects, a colonoscopy was performed to evaluate a positive FOBT. Outcomes were compared between +FOBT group (F-Group) and the asymptomatic screening group (AS-Group). The cost-effectiveness was also calculated using a median estimated standardized worldwide colonoscopy and FOBT cost (rounded to closest whole numbers) of 1000 US and 10 US , respectively. Results . 118/1496 (7.9%) colonoscopies were performed for evaluation of +FOBT. 464/1496 (31%) colonoscopies were performed in AS-Group. In F-Group, high risk adenoma detection rate (HR-ADR) was 15.2%, and 11.9% had 1-2 tubular adenomas. In comparison, the control AS-Group had HR-ADR of 19.2% and 17.7% had 1-2 tubular adenomas. In the FOBT+ group, CRC was detected in 5.1% which was significantly higher than the AS-Group in which CRC was detected in 1.7% (P = 0.03 ). On cost-effectiveness analysis, cost per CRC detected was significantly lower, that is, 19, 666 US in F-Group in comparison to AS-Group 58, 000 US (P < 0.05 ). There were no significant differences in other parameters among groups. Conclusion . Prescreening with FOBT to select elderly for colonoscopy seems to improve the yield and can be a cost-effective CRC screening approach in this subset. The benefit in the risk benefit analysis of screening the elderly appears improved by prescreening with an inexpensive tool.